2019
DOI: 10.1172/jci.insight.131530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosuvastatin on the immune system in healthy volunteers with normal serum cholesterol

Abstract: 5 The CHI Consortium is detailed in the supplemental material. BACKGROUND. HMG-CoA reductase inhibitors (statins) are prescribed to millions of people. Statins are antiinflammatory independent of their cholesterol-reducing effects. To date, most reports on the immune effects of statins have assayed a narrow array of variables and have focused on cell lines, rodent models, or patient cohorts. We sought to define the effect of rosuvastatin on the "immunome" of healthy, normocholesterolemic subjects. METHODS.We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(76 reference statements)
1
12
0
Order By: Relevance
“…Fluvastatin-pretreated donor cells attenuated CTL function in acute graft-versus-host disease mouse model (37). Rosuvastatin suppressed CTL activity in some subpopulations of healthy subjects (38) and HIV-infected patients (39). Direct antiviral effect-inhibition or slowing down viral replication is common to several statins, due to their ability of inhibiting cholesterol production, reducing the availability of some isoprenoids that are essential for regulating the virus life cycle and by inhibiting the activity of regulatory proteins related to virus intracellular life cycle (40).…”
Section: Statins: Tregs Induction-simvastatin and Lovastatin Inducedmentioning
confidence: 98%
“…Fluvastatin-pretreated donor cells attenuated CTL function in acute graft-versus-host disease mouse model (37). Rosuvastatin suppressed CTL activity in some subpopulations of healthy subjects (38) and HIV-infected patients (39). Direct antiviral effect-inhibition or slowing down viral replication is common to several statins, due to their ability of inhibiting cholesterol production, reducing the availability of some isoprenoids that are essential for regulating the virus life cycle and by inhibiting the activity of regulatory proteins related to virus intracellular life cycle (40).…”
Section: Statins: Tregs Induction-simvastatin and Lovastatin Inducedmentioning
confidence: 98%
“…Over the last few years, several pharmacological inhibitors, such as statins and nitrogen-containing BPs have been utilized to control cholesterol metabolism in immune cells. A recent prospective study reported a pro-inflammatory role of rouvastatin in subjects with normal levels of cholesterol [ 91 ], despite the large body of evidence that ascribes anti-inflammatory and immunomodulatory properties to statins, suggesting their key role in the treatment of viral infections [ 92 , 93 ]. Among the immunomodulatory roles of statins, it has firstly recognized their ability to repress the major histocompatibility complex (MHC)-II expression on several cell types, such as macrophages, B and activated T lymphocytes [ 94 ].…”
Section: Interfering With Mevalonate Pathway To Control Anti-viral Immune Responsementioning
confidence: 99%
“…Of special interest will be to address the role of systemic cholesterol in determining the fate of the immune response. In this regard, an interesting study has demonstrated that in healthy individuals, statin treatment increased the levels of pro-inflammatory cytokines in serum, although no functional studies in immune cells were performed [174].…”
Section: Chronic Inflammation: Rheumatoid Arthritismentioning
confidence: 99%